Grotesque tenderness - Cowper, Daniel, 1981- (Hugh MacLennan poetry series., 2019)
"Daniel Cowper's debut poetry collection, Grotesque Tenderness, speaks for an unrooted age, for unrooted people. In these poems, city-dwellers long to ally themselves with some sympathetic culture or the evolutionary logic of nature, but those alliances remain conditional, ambiguous, or dangerous. A tsunami smashes a harbour city into "tide-rows of burning debris"; children chase snakes in summer meadows. The primordial past spins off "rogue by-products and flawed replicas," while lonely office-workers get high on back porches and drink themselves to sleep. The musical and kinetic energy of Grotesque Tenderness is driven by our urge to understand pain and our hunger to reach an imperfect reconciliation with the problems of guilt and suffering. But in the tradition of William Blake, these poems affirm again and again that "the lit world goes on living" and life justifies itself through its own workings. From elegant lyrics of alienation and heartbreak to long-form mythopoeia and lament, these poems approach beauty, ugliness, even criminality in a spirit of wonder and vulnerability."--